Building an Oral Repository of African Immigration Experiences in French: The Griotte Project’s Reparative Historiographic Praxis Through Service-Learning at the University of Central Arkansas - K. Adele Okoli (Journal of Community Engagement and Scholarship)
Central Arkansas and the campus of the University of Central Arkansas are home to a vibrant and growing community of multilingual French speakers of diverse cultural and national identities of West and Central Africa. French serves as an important tool of Black transnational community building, networking, and civic organization in our area. However, Black French speakers in the United States are often erased in official records of the presence and activities of immigrants in Arkansas, as well as from representation in French syllabi. To address and repair these gaps, the author, advanced French students, and community members are building a repository of oral histories of Arkansas African immigration stories in French, activating the university archive as a dynamic teaching and learning space. This article critically reflects on the translation of decolonial, antiracist, and feminist theory into pedagogical praxis through the coordination of a French-language oral history service-learning project from the academic perspective of an associate professor in French in affiliation with the Africana Studies and Gender Studies programs of a predominantly white public regional teaching university in the American South. The UCA Griotte Project entrusts students, the majority of whom are women of African descent, with collaborative leadership of the project to decentralize historical authority and destabilize the teacher/learner dichotomy. When we occupy and open the archive as a space of experiential learning and shared knowledge creation, we are transforming an institutional site of memory to write a more accurate, just, and inclusive history for the future.